The syndrome of `continuous muscle-fibre activity' cured: further studies - Isaacs, Hyam (1974)
Two cases suffering from the syndrome of `continuous muscle-fibre activity' have been followed-up for 14 years. These patients have gradually gone into remission and no longer require therapy. The results of recent histology, histochemistry, and electronmicroscopy, as well as sural nerve biopsy studies, are presented. The sarcoplasmic reticulum calcium binding activity and ATPase activity are normal.